Line × tester analysis for yield and its attributed traits in upland cotton (Gossypium hirsutum L.) - Ahmad, Muhammad; Saeed, Asif; Khakwani, Khunsa; Aqib, Muhammad; Yaqoob, Nabeel; Nadeem, Rujab; Bashir, Ayesha; Rafique, Muhammad Saad (Journal of Pure and Applied Agriculture, 2023)
Cotton production in our country is declining due to produced cultivars that are not well-adapted to changing environmental conditions. New high-yielding, climate-resilient cotton genotypes are needed to enhance our economy. The objective of the study was to assess the effects of gene action, combining ability and heterosis on seed cotton yield and its associated traits. Five lines and three testers of upland cotton (Gossypium hirsutum L.) were used to produce fifteen F1 hybrids using a line × tester mating design. The research was conducted in a randomized complete block design with three replications at Cotton Research Station, Ayub Agricultural Research Institute (AARI), Faisalabad in the Kharif season of 2020-21. The mean squares of all the traits were found significant. The results showed that among the female lines; FH-414 performed best for plant height, days to 50% flowering, boll weight, fiber strength, and fiber length while FH-490 was found best for seed cotton yield and GOT%. Testers concluded that EYE-111 was an excellent general combiner in terms of plant height, monopodial branches, days to maturity, bolls per plant, days to 50% flowering, seed cotton yield, and fiber quality. The cross combinations i.e., FH-492 × CIM-602 for plant height, FH-414 × CIM-602 for fiber fineness and fiber length, and FH-492 × NIAB-SANAB-M for seed cotton yield showed good SCA effects. FH-414 × CIM-602 and FH-415 × EYE-111 depicted maximum heterosis for fiber traits and seed cotton yield, respectively. FH-ANMOL × EYE-111 had shown maximum heterosis for sympodial branches and days to 50% flowering, FH-414 × CIM-602 for GOT% and fiber fineness. all the characters were regulated by non-additive kind of gene action. The above-mentioned genotypes having GCA and SCA effects could be further exploited for hybrid/variety development programs to cope with unexpected climatic conditions.